All Optical Sensors Using Spectral Switching - Kaur, Amandeep (My University, 2016)
Many fascinating phenomena like spectral switching, wave front dislocations occur in the domain of singular optics. The phenomenon of spectral switching has been investigated for linear medium using different input pulses. For the first time, nonlinear medium is used to explore the concept of spectral switching. The spectral switching and fiber optic sensors have been combined. The fiber optic sensors modulate the intensity of light due to the effect of change in pH of the external environment and the results have been used to investigate the dependency of the critical angle on the varying pH. Further the fiber optic relative humidity sensors shifts the dip wavelength of the input pulse and this result has been utilized to explore the behavior of the output when the shifting of the pulse due to spectral switching and the relative humidity is combined. The shift of the output thus found is significant which is ca n help to increase the sensitivity of the fiber optic sensors towards the minute environmental changes. The results found by this collaboration have tremendous applications in data communication, all- optical switching and distant space communications due to the increase in sensitivity towards the variations in external perturbations.
Keywords: spectral switching; blue shift; red shift; sensor